Valuation of enterprise risk management in the manufacturing industry - Zou, Xiang; Isa, Che Ruhana; Rahman, Mahfuzur (Taylor & Francis, 2019)
The paper examines the valuation of enterprise risk management (ERM) through its effects on firm cost and efficiency. Consistent with the empirical evidence, ERM is found to benefit larger firms by reducing earning variability and providing higher returns on equity. The results suggest significant evidence of a value premium attached to effective ERM programmes. It is found that an effective ERM programme adds value to manufacturing firms by mitigating firm cost and enhancing firm efficiency. The results also suggest that the strong valuation effects of ERM are associated with cost management, inventory management, asset management, and cash flow management in China.